The Flames of Time: Bál tímans as Object Biography - Parsons, Katelin Marit (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
The manuscript as narrator in Icelandic children’s novel Bál tímans (2022) belongs to a literary tradition of sentient object narrators who document the domestic spaces in which they circulate. Bál tímans shifts the reader’s focus to normally invisible manuscript owners and users, including women and children, bringing attention to disparities in access created through archive-building activities. In domestic settings, Möðruvallabók is accessible to a broad segment of the Icelandic population through practices of social reading, women’s book ownership, and home education. In the archive, human-manuscript interactions are restricted to a narrow and initially male-only elite. While tensions between preservation and access are resolved when the codex is exhibited in a museum space where it can share its stories with a wider audience, Bál tímans examines what can be lost by bringing cultural objects into archival spaces.